Tracking of leisure-time physical activity during adolescence and young adulthood: a 10-year longitudinal study - Torsheim Torbjørn; Kjønniksen Lise; Wold Bente (BMC, 2008)
Abstract Background The purpose of this study was to show how participation in leisure-time physical activity changes between ages 13 to 23, and to what extent engaging in specific types of sports tracks into young adulthood. Methods The sample comprised 630 subjects who responded to questionnaires at age 13, with seven follow-ups over a 10-year period in the Norwegian Longitudinal Health Behaviour Study. The associations between adolescent participation in global and specific types of leisure-time physical activity were examined by analyses of variance, regression analysis and growth curve analysis. Results The findings suggest that the transition from adolescence to adulthood is, on average, a period of decline in physical activity, but with the decline levelling off into adulthood. The decline was significantly greater among males than females. There were substantial individual differences in the amount of change, in particular among males. Jogging alone and cycling, recreational activities such as skiing and hiking, and ball games, showed a high degree of tracking from age 15 to 23. The findings indicate low associations between participation in specific types of activities during adolescence and global leisure-time physical activity in young adulthood, while participation in several adolescent physical activities simultaneously was moderately related to later activity. Thus, being involved in various types of physical activity may offer good opportunities for establishing lifelong involvement in physical activity, independent of the specific type of activity. Conclusion The observed variation in change might suggest a need for a more targeted approach, with a focus on subgroups of individuals. The group of inactive youth may be considered as a high risk group, and the findings suggest that adolescent males who are inactive early seem likely to continue to be inactive later. The observed heterogeneity in change highlights the limitation of previous approaches to analyzing physical levels over time, and suggests that multilevel analysis should be used in future research on longitudinal data on physical activity.